ANALISIS KOMPARASI PROFITABILITAS PT. BANK RAKYAT INDONESIA SYARIAH, TBK SEBELUM DAN SELAMA MASA PANDEMI COVID-19 - Eva Sumanti; Faisal Amri; Elex Sarmigi (Institut Agama Islam Negeri Kerinci, 2022)
This study aims to analyze the financial perfomace of one of the islamic banks in Indonesia based on the profitability ratios before and during the covid-19 pandemic. As for the object in this study, namely PT. Bank Rakyat Indonesia Syariah Tbk. In this study the authors manage all aspects of the research contained in the profitability ratios including return on asset, return on equity, operating costs, net profit margi and gross profit margin with the hope that the final result of the research can find out whether there is a profitability comparasion at PT. Bank Rakyat Indonesia Syariah before and during covid-19 or there is no comparasion of profitability at PT. Bank Rakyat Indonesia Syariah before and during covid-19. As for this type of research is a type of comparative descriptive research with a quantitative approach. The data contained in this study is non-parametric data with the Wilxocon test analysis technique using SPSS. With the results of the study there is a comparasion of profitability at PT. Bank Rakyat Indonesia Syariah Tbk, before and during covid-19 on the ratio return on asset while in other research aspects such as retun on equity, operating costs,net profit margin and gross profit margin there is no comparasion of profitability at PT. Bank Rakyat Indonesia Syariah Tbk,before and during covid-19.